CHILDREN’S DEPRESSION RATING SCALE-REVISED (CDRS-R) – DEVELOPMENT OF THE LATVIAN VERSION AND PSYCHOMETRIC PROPERTIES IN A CLINICAL AND NON-CLINICAL SAMPLE OF ADOLESCENTS - Elsiņa, Inese; Martinsone, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Depression is one of the most widespread mental disorders worldwide. Adolescence is a vulnerable period for developing depression. It is associated with a number of challenges in biological, psychological and social areas. Valid and reliable measurement instruments are required for assessment of symptoms of depression in clinical samples of adolescents in Latvia. Children's Depression Rating Scale Revised (CDRS-R, Posnanski & Mokros, 1996) is a semi-structured, clinician-rated interview for assessment of depression in children and adolescents. While the CDRS-R is the most widely used rating scale for research and clinicians’ practical use worldwide, there's no validated version in Latvian language available yet. The aim of this study is to present the reliability and validity of the Latvian version of CDRS-R in the adolescent age group. Twenty-five adolescents (aged 12-17) with diagnosis of depressive disorder (inpatients and outpatients) and twenty healthy controls were assessed with CDRS-R by clinical psychologist. Reliability and validity were calculated and analyzed: Cronbach’s alpha, Weighted Kappa, Spearman's rank correlation coefficient, Receiver operating characteristic (ROC). The Latvian translation of CDRS-R showed good psychometrical properties. Internal consistency for the CDRS-R was high. CDRS-R total score was significantly correlated with CDI both in nonclinical and clinical sample. There was a significant concordance with the reference standard of ICD-10 diagnosis.